PENERAPAN SANKSI ADAT PERCERAIAN MASYARAKAT DAYAK KANAYATN DI DESA PAKU RAYA KABUPATEN LANDAK - NIM. A1011211053, DONI ERMANSYAH (Jurnal Fatwa Hukum, 2025)
Abstract Divorce can only be granted if there are strong reasons for the husband or wife to seek divorce and will result in customary sanctions. However, in reality, there are married couples in Paku Raya Village, Kuala Behe District, Landak Regency who have divorced and have been subject to customary sanctions, but the violators do not want to pay the customary sanctions. This study aims to provide information about the implementation of customary divorce among the Dayak Kanayatn community in Paku Raya Village, Kuala Behe District, Landak Regency. It also aims to reveal the reasons why the violators of custom do not pay the customary sanctions. Furthermore, it aims to reveal the legal consequences of divorce in Paku Raya Village, Kuala Behe District, Landak Regency. Finally, it aims to reveal the efforts made by customary officials against violators who do not pay customary sanctions. This study uses an empirical legal method with a descriptive analytical approach through interviews, questionnaires, and literature studies. The results of this study show that the implementation of customary divorce in Paku Raya Village, Kuala Behe District, Landak Regency has basically been carried out in accordance with the applicable provisions and has been implemented by customary officials; that the main reason for customary violators not paying or fulfilling customary sanctions is because the sanctions are considered too severe or they feel aggrieved and the violators feel that they are not at fault in committing divorce; The legal consequences of the dissolution of a customary marriage in Paku Raya Village, Kuala Behe District, Landak Regency are that the divorcing party will be subject to customary sanctions, and these sanctions will also apply to children born during the marriage and the distribution of inheritance acquired during the marriage. That efforts made by customary officials against violators If the customary violator remains unwilling to pay or comply with the sanctions that have been decided, the case will be assisted in its resolution by the Timanggung as the holder of higher authority in the customary structure. Keywords: Divorce Traditional, Dayak Kanayatn Abstrak Perceraian hanya dapat dilakukan apabila terdapat alasan-alasan yang kuat untuk dipakai oleh suami atau istri untuk melakukan perceraian dan akan mengakibatkan sanksi adat. Akan tetapi pada kenyataannya terdapat pasangan suami istri di Desa Paku Raya Kecamatan Kuala Behe Kabupaten Landak yang melakukan perceraian dan telah ditetapkan sanksi adat akan tetapi pelanggar adat tersebut tidak ingin membayar sanksi adat. Penelitian ini bertujuan untuk Untuk informasi tentang gambaran pelaksanaan perceraian adat pada masyarakat Dayak Kanayatn di Desa Paku Raya Kecamatan Kuala Behe Kabupaten Landak. Untuk mengungkapkan alasan pelanggar adat tidak membayar sanksi adat. Untuk mengungkapkan akibat hukum yang melakukan perceraian di Desa Paku Raya Kecamatan Kuala Behe Kabupaten Landak. Untuk mengungkapkan upaya yang dilakukan oleh fungsionaris adat terhadap pelanggar yang tidak membayar sanksi adat. Penelitian ini menggunakan metode hukum empiris dengan pendekatan deskriptif analisis melalui wawancara, angket, serta studi kepustakaan. Hasil penelitian ini Bahwa Pelaksanaan adat perceraian di Desa Paku Raya Kecamatan Kuala Behe Kabupaten Landak pada dasarnya telah berjalan sesuai ketentuan yang semestinya dan dilaksanakan oleh fungsionaris adat; Bahwa Alasan utama pelanggar adat tidak membayar atau memenuhi sanksi adat adalah karena sanksi tersebut dianggap terlalu berat atau merasa dirugikan dan pelanggar merasa dirinya tidak bersalah dalam melakukan perceraian; Bahwa Akibat hukum dari putusnya perkawinan adat di Desa Paku Raya Kecamatan Kuala Behe Kabupaten Landak adalah pihak yang menceraikan akan dikenakan sanksi adat dan terhadap anak yang dilahirkan dalam perkawinan serta pembagian harta warisan yang diperoleh selama masa perkawinan; Bahwa Upaya yang dilakukan oleh fungsionaris adat terhadap pelanggar Apabila pihak pelanggar adat tetap tidak bersedia membayar atau memenuhi sanksi yang telah diputuskan, maka perkara tersebut akan dibantu penyelesaiannya oleh Timanggung sebagai pemegang kewenangan yang lebih tinggi dalam struktur adat. Kata Kunci: Adat Perceraian, Dayak Kanayatn